2022
DOI: 10.1007/s00330-022-08919-9
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning–based acceleration of Compressed Sense MR imaging of the ankle

Abstract: Objectives To evaluate a compressed sensing artificial intelligence framework (CSAI) to accelerate MRI acquisition of the ankle. Methods Thirty patients were scanned at 3T. Axial T2-w, coronal T1-w, and coronal/sagittal intermediate-w scans with fat saturation were acquired using compressed sensing only (12:44 min, CS), CSAI with an acceleration factor of 4.6–5.3 (6:45 min, CSAI2x), and CSAI with an acceleration factor of 6.9–7.7 (4:46 min, CSAI3x). Moreov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…49,50 Most are based on the image domain SENSE model for coil combination or for building the DC term. [51][52][53] Some methods attempt to utilize the intrinsic relationship between coils using neural networks, without explicitly estimating the sensitivity maps of the coils. [54][55][56][57][58][59] Other methods attempt to simultaneously estimate coil sensitivity maps and perform image reconstruction.…”
Section: Pimentioning
confidence: 99%
“…49,50 Most are based on the image domain SENSE model for coil combination or for building the DC term. [51][52][53] Some methods attempt to utilize the intrinsic relationship between coils using neural networks, without explicitly estimating the sensitivity maps of the coils. [54][55][56][57][58][59] Other methods attempt to simultaneously estimate coil sensitivity maps and perform image reconstruction.…”
Section: Pimentioning
confidence: 99%
“…Notably, Fervers et al observed significantly improved subjective image quality for 3D T2-weighted images of the lumbar spine when employing CS-AI, as opposed to CS-based reconstruction [ 20 ]. Moreover, studies focusing on MRI of the ankle and prostate have reported enhanced objective and subjective image quality for sequences reconstructed with CS-AI [ 21 , 22 ]. While CS-AI yields images with superior subjective image quality in comparison to CS, it is important to consider that excessively high acceleration levels may compromise diagnostic quality.…”
Section: Discussionmentioning
confidence: 99%
“…Third, it is important to note that our study did not incorporate objective measures of image quality. Previous research by Foreman et al has discussed that traditional objective quality measures, such as signal-to-noise ratio, may not accurately reflect the quality of accelerated images generated through DL techniques [ 21 ]. Interestingly, Foreman et al [ 21 ] observed an increase in signal-to-noise ratio with higher acceleration levels, despite a decrease in subjective image quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This CNN is applied prior coil channel combination, removing the noise from the images to obtain good image quality from accelerated acquisitions ( 29 ). The Adaptive-CS-Network employed in this work was pre-trained on 740,000 sparsifying MR images using both 1.5T and 3T images of various anatomies and contrasts ( 25 , 33 ). The prototype was adapted and optimized to run on up-to-date standard reconstruction hardware available in our 3T MR scanner ( 31 ).…”
Section: Methodsmentioning
confidence: 99%